2021
DOI: 10.2478/aoas-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Macro-Minerals, Other Selected Serum Markers of Bone Profile and Milk Components of Dairy Cows During Late Lactation

Abstract: Testing blood and milk parameters as well as analysing the relationships among these markers is very useful for monitoring the internal homeostasis and health in high-yielding dairy cows during various production periods. The aim of the study was to assess the correlations (relationships) among macro-minerals, such as calcium (Ca), inorganic phosphorus (P), magnesium (Mg), other selected bone profile markers, such as total protein (TP), albumin, activity of alkaline phosphatase (ALP) measured in serum and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…WBC -white blood corpuscles, RBC -red blood corpuscles, PLT -platelets, HGB -hemoglobin concentration, HCT -hematocrit, MCV -mean red corpuscle volume, MHC -mean red corpuscular hemoglobin content, MCHC -mean corpuscular hemoglobin concentration in erythrocytes. *Values of milk parameters such as milk production, CFU -colony forming units, SCC -somatic cell count, MF -milk fat, MP -milk protein, ML -milk lactose, Solids -milk solids, SNF -milk solids non-fat as a necessary comparative basis for correlation assessment also for other blood parameters and profiles characterizing the functions of other organs or other body systems were published respectively [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WBC -white blood corpuscles, RBC -red blood corpuscles, PLT -platelets, HGB -hemoglobin concentration, HCT -hematocrit, MCV -mean red corpuscle volume, MHC -mean red corpuscular hemoglobin content, MCHC -mean corpuscular hemoglobin concentration in erythrocytes. *Values of milk parameters such as milk production, CFU -colony forming units, SCC -somatic cell count, MF -milk fat, MP -milk protein, ML -milk lactose, Solids -milk solids, SNF -milk solids non-fat as a necessary comparative basis for correlation assessment also for other blood parameters and profiles characterizing the functions of other organs or other body systems were published respectively [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…Different researchers indicate that both blood and milk tests are very useful in monitoring of health, as well as in the diagnosis of health problems in dairy cows [11,21,24]. The results of various blood tests analyzed in relation to the clinical condition of the cows, their milk yield, mammary gland quality and milk composition are particularly important in cattle practice from the point of view of animal welfare and the quality of dairy products [17,25,27,28]. In addition a milk sample can have great potential in detection of mastitis, assessing the composition of milk as well as in predicting blood metabolites and the metabolic status of cows [2,3,15,20,26] .…”
Section: Introductionmentioning
confidence: 99%
“…The available scientific literature does not provide detailed data on the simultaneous testing of blood and milk, especially in late lactation in dairy cows when tests are repeated over a few days. In our previous studies, the usefulness of such a model was demonstrated in the assessment of the relationship between serum markers of liver function and milk composition (35), as well as the relationship between macro minerals, selected serum markers of bone profile, and components of milk from dairy cows in late lactation (34).…”
mentioning
confidence: 99%